Scholars & rebels : in nineteenth-century Ireland - Eagleton, Terry, 1943- (Oxford : Blackwell Publishers, 1999)
"Terry Eagleton's book provides a novel account of Ireland's neglected 'national' intellectuals. This extraordinary group, including such figures as Oscar Wilde's father William Wilde, Charles Lever, Samuel Ferguson, Isaac Butt and Sheridan Le Fanu, was a kind of Irish version of 'Bloomsbury' (they were doctors, lawyers, economists, writers and amateurs, rather than academics). Their work, much of it published in the pages of the Dublin University Magazine, was deeply caught up in networks of kinship, shared cultural interests, and intersecting biographies in the outsized village of nineteenth-century Dublin.
Eagleton explores the preoccupations of this remarkable community, in all its fascinating ferment and diversity, through the lens of Antonio Gramsci's definitions of 'traditional' and 'organic' intellectuals, and maps the nature of its relation to the young Ireland movement, combining his account with some reflections on intellectual work in general and its place in political life."--BOOK JACKET.
Includes bibliographical references and index.
Keywords: English literature -- Irish authors -- History and criticism